2020
DOI: 10.1126/science.aay6637
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the past and considering the future of chemicals in the environment

Abstract: Knowledge of the hazards and associated risks from chemicals discharged to the environment has grown considerably over the past 40 years. This improving awareness stems from advances in our ability to measure chemicals at low environmental concentrations, recognition of a range of effects on organisms, and a worldwide growth in expertise. Environmental scientists and companies have learned from the experiences of the past; in theory, the next generation of chemicals will cause less acute toxicity and be less e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 56 publications
0
97
1
Order By: Relevance
“…Routes may be through direct application and run-off of agrochemicals (Kohler and Triebskorn, 2013;Elias et al, 2018), intended or accidental industrial releases (Batty and Hallberg, 2010), or via waste and wastewater infrastructure, such as for down the drain products passing through wastewater treatment (Munoz et al, 2008;Gardner et al, 2012), or in leachates from landfills (Masoner et al, 2014;Kummerer et al, 2019). As well as their recognized health effects (Landrigan et al, 2018), pollutant chemicals can also affect wildlife species and ecological communities (Hayes et al, 2018;Johnson et al, 2020), placing real costs on ecosystem functions and services (Wang et al, 2019). For example, Pretty et al (2000) identified external costs of £120 M and £16 M for pesticide and fertilizer applications to the United Kingdom drinking water supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Routes may be through direct application and run-off of agrochemicals (Kohler and Triebskorn, 2013;Elias et al, 2018), intended or accidental industrial releases (Batty and Hallberg, 2010), or via waste and wastewater infrastructure, such as for down the drain products passing through wastewater treatment (Munoz et al, 2008;Gardner et al, 2012), or in leachates from landfills (Masoner et al, 2014;Kummerer et al, 2019). As well as their recognized health effects (Landrigan et al, 2018), pollutant chemicals can also affect wildlife species and ecological communities (Hayes et al, 2018;Johnson et al, 2020), placing real costs on ecosystem functions and services (Wang et al, 2019). For example, Pretty et al (2000) identified external costs of £120 M and £16 M for pesticide and fertilizer applications to the United Kingdom drinking water supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…However, ecologists, ecotoxicologists, and risk analysts must continue to foster research on several fronts to further integrate indirect effects into the fabric of ecotoxicology and strengthen our understanding of contaminant effects on populations, communities, and ecosystems. Most research in ecotoxicology has been at the individual-effects level [117], and methods to improve toxicity models continue to be developed. For example, models based on species-level traits and bioenergetics have the potential to improve predictions of species-level responses to various chemicals [114,118], and databases associated with toxic effects that include traditional toxicological information and the results of toxicogenomic or other molecular methods that identify the mode of toxic action are being developed, in some instances with computational modeling [119,120].…”
Section: Final Comments On Indirect Effectsmentioning
confidence: 99%
“…Although chemicals have improved the quality of human life, their continuous development and corresponding environmental pollution leads to detrimental effects through a variety of exposure pathways. Still, the determination of their persistence, transformation, and accumulation behavior in different environmental compartments remains a challenge for defining their complete associated risks, since not all the chemicals are equivocal nor similar in exposure [2,3]. Moreover, the aquatic environment encompassed a variety of molecules that drive continuous interaction with chemical pollutants and the mixtures are expected to cause severe effects greater than their own individual threshold limits resulting from the "concentration addition and independent action" phenomenon of the chemicals with similar and different modes of action, respectively [4,5].…”
Section: Introductionmentioning
confidence: 99%